Attitudes toward uncertain results from prenatal exome sequencing: a national survey among healthcare professionals working in the prenatal setting - Lu, Dongfang; Yang, Jing; Shen, Wei; Chen, Min (Frontiers in Medicine, 2024)
Objective The objective of this study was to investigate the attitudes of healthcare professionals (HPs) working in the prenatal setting toward uncertain results (UR) from prenatal exome sequencing (pES) in China. Methods We conducted a national survey among HPs working in the prenatal setting. UR in our study include variants of uncertain significance (VUS), variants with variable penetrance/expressivity (VVPE), and secondary findings unrelated to the indication for testing (SFs). A total of 285 questionnaires that met the inclusion criteria were collected. Data were analyzed using IBM SPSS Statistics 26. Results When performing the pre-test counseling, only 7.4% of HPs mentioned the possibility of VUS, 6.3% discussed the possibility of VVPE, and 7.4% introduced the SFs with parents with the option to not report these variants. In post-test counseling, 73.0–82.8% HPs discussed with the parents but did not make any recommendations for managing the pregnancy after reporting UR (73.0% for VUS, 82.8% for VVPE, 74.7% for SFs, respectively). Conclusion Most parents did not have the option of opting out of reporting UR from pES in pre-test counseling. UR did not influence the pregnancy recommendation made by most HPs. Establishing national guidelines for reporting UR from pES and developing strategies to improve counseling skills may help HPs manage UR.